EVALUASI KUALITAS PATHFINDER SEBAGAI ALAT TEMU BALIK INFORMASI DI PERPUSTAKAAN UIN SUNAN KALIJAGA - Sri Rohyanti Zulaikha; Ulfatun Madya (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
Pathfinder is a kind or reference source in process or re-meeting behind the information at the library. The aim of studied is evaluation for pathfinder with eight dimensions of service satisfaction evaluation, there are performance, features, reliability, confermance to specification, easthetic, and percieved quality at Library of Sunan Kalijaga Islamic University by Voice Of Customer in House Of Quality of Quality Function Deployment method. Result this studied is the satisfaction assessment of user about technical characteristics (Hows) is information content in the pathfinder and repair for collection synopsis quality for the convenience of the user. An indicator of declared dissatisfied, it is on product durability of the user need (Whats). The researcher suggest is, digitalization pathfinder at the toolbar digital cillection of www.lib.uin-suka.ac.id.